2020
DOI: 10.1103/physrevphyseducres.16.010110
|View full text |Cite
|
Sign up to set email alerts
|

Scientists suggest insertion of nanoscience and technology into middle school physics

Abstract: The goal of this research is to provide a rich set of connections between two fields: (i) Nanoscale science and technology (NST) and (ii) topics from a common middle school physics curriculum. NST is emerging as one of the most promising new fields of the 21st century, which is one of the many arguments for including NST topics in secondary science education. A specially designed guided discourse with NST scientists was used to produce a map of connections between the two fields. During the discourse, the scie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 16 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…Many curriculum designers consult leading scientists to integrate contemporary research into the curriculum. For example, Yonai and Blonder [23] consulted with scientists to build connections between a middle school nanoscale science and technology (NST) curriculum and their contemporary research-driven insights.…”
Section: Conceptual Profile Theorymentioning
confidence: 99%
“…Many curriculum designers consult leading scientists to integrate contemporary research into the curriculum. For example, Yonai and Blonder [23] consulted with scientists to build connections between a middle school nanoscale science and technology (NST) curriculum and their contemporary research-driven insights.…”
Section: Conceptual Profile Theorymentioning
confidence: 99%
“…The SEM device holds the potential of opening a window into contemporary science for teachers and their students (6). The SEM f2f course used this potential to present selected contemporary work done at a research institute.…”
Section: Contentmentioning
confidence: 99%
“…The concept of ''characterization methods'' refers to observing, imaging, studying, and manipulating the size of nanomaterials (4). Several studies with different approaches indicated characterization methods as a fertile context for communication of contemporary science in secondary education (5)(6)(7)(8).…”
Section: Introduction a Use Of Sem In Science And Science Teachingmentioning
confidence: 99%
“…NST is, in this regard, intrinsically multidisciplinary, often utilizing knowledge from chemistry, physics, engineering, biology, medicine, and ecology, to name a few disciplines [ 5 ]. There is also a continuing need to update university- and school-level curricula with contemporary scientific topics, and nanoscience and nanomaterials are no exception [ 6 , 7 , 8 , 9 ]. If we take the chemical synthesis and properties of nanoparticles as an example, then many papers in journals dedicated to teaching have provided introductions via short experiments aimed at undergraduates and even high school students [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Table 1. Key concepts of nanomaterial science and technology (adapted from [9]) and their educational links to nanoporous silicon fabrication, properties, and applications (applications in italics were highlighted by the Delphi study of nanotechnology uses [21]). We first provide a brief background to the nanomaterial and its parent semiconductor, then cover how synthesis options have now expanded to include safer and more accessible routes, highlight two of the tunable properties of nanoporous silicon that have given rise to substantial interest in academia and industry, and then summarize application areas.…”
Section: Introduction 1nanomaterials Educationmentioning
confidence: 99%